Adding experiential layers to the transnational-athlete concept: A narrative review of real-world heterogeneous mobility experiences. (January 2022) - Bobrownicki, Ray; Valentin, Stephanie
Abstract: Objective: With rising mobility and greater recognition of the diversity of origins, cultures, and outlooks, there has been increasing interest in transnational perspectives in sport psychology scholarship and practice. Based on personal and professional experiences, however, we are concerned that there are diverse transnational-athlete perspectives that have not yet been explored in the literature which are also often restricted by traditional nation-based sporting policies, organisations, and events. As cultural awareness and understanding may enhance consultancy effectiveness and enable the construction of heretofore unrealised identities for athletes, in this paper we seek to expand upon the heterogeneity of athlete experiences relating to mobility by exploring real-world cases of transnational athletes and how their experiences fit into current sporting structures. Design: Narrative review and commentary. Results: Three identity orientations that showcase transnational diversity are identified: postnational, intranational, and non-national. Key characteristics and challenges relating to these for athletes, coaches, and practitioners are exemplified and discussed. Conclusion: To enhance rapport and inclusivity, researchers and practitioners should not only consider experiences, perceptions, and constructed identities of postnational, intranational, and non-national athletes, but also seek to understand how these interact with or are influenced by environmental and structural factors. Highlights: We explore real-world cases of transnational athletes to showcase diversity of experiences. We propose three transnational identity orientations: postnational, intranational, and non-national. For rapport and inclusivity, practitioners should explore experiences and identities of these groups. Researchers should examine impact of current policies, practices, and structures on these identities.